Temporal and spatial changes and environmental mechanism of cholera epidemic in Hunan province during the period of Republic of China(民国时期湖南省霍乱流行的时空变迁特征及环境机理) - 杨婷婷(YANG Tingting); 殷淑燕(Shuyan YIN) (Zhejiang Daxue xuebao. Lixue ban)
The time series of cholera epidemics in various counties of Hunan province during the period of Republic of China was sorted out through the Collection of Historical Data of Epidemic disasters in China for Three Thousand Years (Republic of China Volume). Combined with data on meteorological disasters, war, population, traffic etc., hot spot analysis, center of gravity migration model and Spearman correlation analysis were used to explore the temporal and spatial characteristics and influencing factors of cholera epidemics. The results show that cholera mainly occurred in summer and autumn in Hunan province during the period of Republic of China, and the annual epidemic frequency was 86.84%, and the long-term fluctuation increased, and there were three cholera peaks in 1919-1920, 1931-1933 and 1938-1946. The cholera epidemic gradually became more and more serious, from the early dispersed distribution to the concentrated continuous epidemic, the breadth of cholera distribution increased from 22.08% to 75.32%. In terms of spatial distribution, the center of gravity of cholera epidemic in Hunan province during the period of Republic of China was always in the central plain, and showed a trend of migration from north to south, the hot spots located on the Dongting Lake Plain and Xiangjiang River basin. The cold spots were mainly concentrated in the western counties and the southeast of Hunan province. The correlation analysis showed that temperature, war, flood and other changes over time caused the time variation characteristics of cholera disaster more and more serious, and the regional differences such as population density, river length, transportation convenience and altitude determined the spatial characteristics of the cholera epidemic along the Xiangjiang River in Hunan province, from southwest to south to northeast. In summary, the epidemic characteristics of cholera in Hunan province during the period of Republic of China were the result of the superimposed influence of natural and social environmental factors.通过《中国三千年疫灾史料汇编》（民国卷），整理得到民国时期湖南省各县霍乱流行的时间序列，并结合气象灾害、战乱、人口、交通等数据，利用热点分析、重心迁移模型和Spearman相关分析，探究了霍乱流行的时空变迁特征及其影响因素。结果表明：民国时期湖南省霍乱主要在夏秋两季流行，年流行频度为86.84%，且长期波动上升，出现了1919—1920年、1931—1933年、1938—1946年3次高峰期。霍乱流行逐渐严重，由早期的分散分布逐渐发展为集中连片流行，分布广度由22.08%上升至75.32%；在空间分布上，民国时期湖南省霍乱流行的重心始终处于中部平原地区，并呈由北向南迁移的趋势，热点区在洞庭湖平原及湘江流域；冷点区主要集中在湖南省西部各县及东南部。相关分析结果表明，平均气温、战乱、洪涝灾害等因素随时间的变化造成了霍乱灾害越来越严重的时间变化特征，而人口密度、河道长度、与主要交通线的距离、海拔高度等区域差异决定了湖南省霍乱流行热点区域沿湘江由西南、南部向东北方向呈条状分布的空间特征。民国时期湖南省霍乱流行特征是自然环境因素与社会环境因素叠加作用的结果。